Educação musical e autismo: um estudo sobre o desenvolvimento de crianças autistas na musicalização infantil - Aires Filho, Sergio Alexandre de Almeida (2020)
The specific literature of children with autism has pointed out a significant set of characteristics of this population. Among them, the following can be highlighted: limitations in language and emotional reciprocity; reduced or absent imitation of other people's behavior; the reduced, absent or atypical use of eye contact; simple motor stereotypes, such as the repetitive use of objects; repetitive speech; resistance to change; highly limited and fixed interests; hyper or hyporeactivity to sensory stimuli, among other characteristics. Such aspects are also present in children's teaching and learning situations, becoming in many cases the barriers to be overcome as part of the training objectives. Thus, in addition, we highlight another perspective in the literature that points to family participation as an important factor in the construction of more effective educational processes in the pursuit of such goals. In this context, this work is fundamentally focused on the educational practices of children's musicalization, inserting themselves in the field of more specific studies of special musical education. Here, the central objective is to discuss how the development of autistic children happens in the music class at the Instituto Revertendo Autismo and how parents perceive this development. To this end, a qualitative research was conducted with fieldwork conducted from July to December 2019. The fieldwork was based on the observation and conduct of music classes at the Institute, as well as the application of semi-structured interviews with the parents. The work was based on the studies of music education, special music education, among other related areas that made it possible to understand the themes worked. The results of the research show us that music plays a significant role in the momentary reduction of characteristics of autism, promoting social interaction and language development, with its practice being of fundamental importance in the first years of life of the autistic child. In addition, we realize the importance of parents' participation in music classes as a way to participate in their children's childhood and serve as an example when carrying out musical activities and games, arousing children's interest and development.